Exploring Strategies to Improve Adherence to Immunization Schedule: A Study among Children Attending Maternal and Child Health Clinic at Kenyatta National Hospital, Nairobi, Kenya - Esther Cheptanui Muathe; Mary Kamau; Eve Rajula (International Journal of Pediatrics)
Background. Globally, immunization is among the major contributors to public health, preventing 20% of childhood mortality annually. The highest fatality rates from vaccine preventable diseases are usually among children under five. Despite immunization guidelines put in place by the World Health Organization, globally, 1.5 million children die annually related to inadequate vaccination coverage. Existing literature indicate that there is an increase in nonadherence to immunization schedule in developing countries, and therefore, there is an increased demand to improve adherence to immunization schedule. Objective. To explore strategies that will improve adherence to immunization schedule among children under 24 months attending the Maternal and Child Health clinic at Kenyatta National Hospital. Methods. A cross-sectional mixed method study involving caregivers (n=214) of well babies attending the Maternal and Child Health clinic. Data was collected using semistructured questionnaires, focus group discussions, and key informant interviews and analyzed using SPSS V.20. Results. There was a significant relationship between the level of education and marital status of the caregivers and adherence to immunization schedule. Barriers found that is related to adherence to immunization schedule included far distance from health facility, baby’s sickness, and vaccine stock-outs while employment of a caregiver was a constrainer factor. Conclusion. The enabling factors to current strategies of improving adherence to immunization schedule were having more health facilities near residential areas, using text messages reminders a day before the clinic date to remind caregivers of the due date for the clinic, and constant availability of vaccines. The health system strategies that would improve adherence to immunization schedules were more flexible clinic hours, availability of vaccines on daily basis, phone call reminders by health care providers, and increasing awareness on the importance of both vaccinations and adherence to immunization schedule.